Data Management Application Research and Community Service Development Center (P4M) Web Based on STMIK Dipanegara Makassar - Cucut Susanto; Nur Salman; Po Abas Sunarya (CCIT (Creative Communication and Innovative Technology) Journal, 2021)
STMIK Dipanegara Makassar as an IT campus should rightly maximize the use of technology in an effort to improve the quality and productivity of lecturers and students. One of them is at the Research and Community Service Development Center (P4M) unit that handles the Field Work Plus lectures as well as the Research and Community Service of Internal Lecturers. Where the administration of data management is still using manual methods which of course can cause problems such as lost files, data collection that takes a long time and constrained information dissemination. Therefore, there needs to be an application that can manage administrative data where the application is built in the form of a web so that it can be used as a medium for disseminating information about activities that are the responsibility of P4M. This study uses observations and interviews in gathering data. With this system, P4M no longer needs to use manual methods in managing its administrative data and can use the system as a medium for spreading information.